2
$\begingroup$

Find the value of $$\sum^{n=k}_{n=1}\tan^{-1}\frac{4}{4n^2+3}$$

I tried multiplying numerator and denominator by $n^2$, but got nothing. How do I split the term inside $\tan^{-1}$?

$\endgroup$
6
$\begingroup$

The trick is to turn it into a telescoping series. Since

$$\tan (a - b) = \frac{\tan a - \tan b}{1+\tan a \tan b},$$

the thing to try is to write $\frac{4}{4n^2+3}$ in the form $\frac{c_n-c_{n+1}}{1+c_nc_{n+1}}$. A little experimentation leads to

$$c_n = \frac{1}{n-\frac{1}{2}}.$$

| cite | improve this answer | |
$\endgroup$
3
$\begingroup$

I tried again and got the answer. $\frac{4}{4n^2 + 3} = \frac{1}{n^2 + 3/4} = \frac{1}{1 + n^2 -1/4} = \frac{1}{1 + (n+1/2)(n-1/2)} = = \frac{(n+1/2) - (n-1/2)}{1 + (n+1/2)(n-1/2)}$

$$\sum^{n=k}_{n=1}\tan^{-1}\frac{4}{4n^2+3} = \sum^{n=k}_{n=1}\tan^{-1}\frac{(n+1/2) - (n-1/2)}{1 + (n+1/2)(n-1/2)} = \boxed{\tan^{-1}(k+1/2) - \tan^{-1}1/2}$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.